Evaluation of ENACTS-Rwanda: A new multi-decade, high resolution rainfall and temperature data set—Climatology - Siebert, Asher; Dinku, Tufa; Vuguziga, Floribert; Twahirwa, Anthony; Kagabo, Desire M.; Corral, John del; Robertson, Andrew W. (Wiley, 2019)
There were a large number of active meteorological stations in Rwanda prior to the mid‐1990s and since around 2010. However, from around the time of the Rwandan genocide in 1994 throughout the late 2000s, the number of active stations was greatly reduced. To address temporal and spatial gaps in meteorological observation in several African nations (including Rwanda), the ENACTS (Enhancing National Climate Services) initiative reconstructs rainfall and temperature data by combining station data with satellite rainfall estimates, and with reanalysis products for temperature. Bias correction factors are applied to the satellite and reanalysis data and the merged final product is spatiotemporally complete from the early 1980s to the present at a high spatial resolution (4–5 km). This paper offers the first analysis of Rwanda's climatology using this new ENACTS data set for 1981–2016. The temperature and rainfall climatology of Rwanda are analysed at both annual and seasonal timescales as are the climatological influences of topography and regional winds. Climatology maps of mean rainfall intensity, rainy day, 5‐day dry spell and extreme rain day (20+mm) frequency are shown, and spatial pattern correlations are analysed. The rainfall climatology of Rwanda exhibits a clear seasonal bimodality typical of the East Africa region. Topography has a significant effect with the more mountainous, higher‐elevation western part of the country being consistently cooler and wetter than the lower, flatter eastern region. Southeasterly winds tend to prevail over Rwanda, but in some seasons, the climatological winds weaken and shift direction. While spatial patterns of rainy day and dry spell frequency are consistent with the spatial patterns of the seasonal rainfall total, climatologically drier regions have a higher mean rainfall intensity on rainy days. This analysis demonstrates the value of the ENACTS product and illustrates climatological patterns in Rwanda over the last 30 years.